PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA UD. MAWAR DESA TUINDRAO KECAMATAN AMANDRAYA - Hendrik Kuasa Sihura; Arwan Karier Harefa; Yulimina Giawa (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2023)
The research objective was to determine the effect of service quality on customer satisfaction at UD Mawar, Tuindrao village. Type of research: quantitative with a descriptive approach. The research instrument is a questionnaire. The consumer research sample is UD Mawar, Tuindrao Village, Amandraya District. Data analysis techniques are validity test, reliability test, correlation test, coefficient of determination test, regression test, and hypothesis testing. The research results of the researchers are as follows: the tcount obtained is 7.586 with a ttable of 2.069. or Ha is accepted, which means that there is an influence of service quality on customer satisfaction at UD Mawar, Tuindrao village. The conclusion of the study is that there is an effect of service quality on customer satisfaction at UD Mawar in Tuindrao village. Researchers' suggestions: 1) For UD Mawar in Tuindrao village, they should maintain service quality and customer satisfaction, one of which is by choosing employees who have the ability to provide services, add types of products and pay more attention to the quality of the products sold so that they can increase consumer satisfaction. 2) For future researchers, it is suggested to be able to use even more data, so that the research is even better and it is hoped that it can develop the results of this research and become a reference.